Sejarah Perkembangan Pendidikan Islam (Kasus Madrasah Nidham al-Mulk) - Hasaruddin Hasaruddin (Universitas Islam Negeri Alauddin Makassar, 2015)
In the history of human life, there is always requires the progress and development in order to improve their living standards. For that matter, there are the ideas about transfer, preservation and development of human culture, in order to improve the quality of human resources in the future. Therefore, in the history of the growth and development of society, education is a great topic which is always gets an attention in order to improve the human resources, trough by the times.Nidham al-Mulk who was very concerned with the progress and development of society, had strived to continuously maintained and improved the human resources in his era. In that time, education implemented in various mosques, but because the number of students and in order to maintain the quality of worshipping to the God then, Nidham al-Mulk founded madrasah to response the demands of society in order to study well, namely Nidhamiah.